A Minority of One. (2nd November 2022) - Devji, Faisal
ABSTRACT: The dominance of empire in contemporary scholarship has edged out the study of nationalism as its historical foe and alleged successor. Rather than being confined to the past, empire has been revived to describe the present and future, even serving as the predecessor to globalization. Yet it was arguably nationalism that served as the enemy of many movements we define as anti-colonial in the last century. Instead of representing a distinctive form of power, empires were often seen as being corrupted by nationalism, whose majoritarian violence had to be opposed in the name of minorities. At the forefront of these struggles internationally were Muslim minorities whose political thought drew upon anarchist ideas to combat nationalism as the true face of empire.